Monetary Policy, Bank Leverage, and Financial Stability - Valencia, Fabian (IMF Working Papers; Working Paper ;, 2011)
This paper develops a model to assess how monetary policy rates affect bank risk-taking. In the model, a reduction in the risk-free rate increases lending profitability by reducing funding costs and increasing the surplus the monopolistic bank extracts from borrowers. Under limited liability, this increased profitability affects only upside returns, inducing the bank to take excessive leverage and hence risk. Excessive risk-taking increases as the interest rate decreases. At a broader level, the model illustrates how a benign macroeconomic environment can lead to excessive risk-taking, and thus it highlights a role for macroprudential regulation.